Antithrombotic agent’s effects in thrombotic events caused by Covid-19: A systematic review - Ramos, Mariana Cristina de Assis; Alves, Caio César de Souza; Silva, Fernando de Sá; de Castro, Sandra Bertelli Ribeiro (Seven Editora, 2023)
There is an association between COVID-19 and an increased risk of thrombotic events. However, the incidence of such events changes due to the severity of the disease. The aim of this paper was to evaluate the effects of antithrombotic agents on thrombotic events caused by COVID-19. This is a systematic review, with descriptive qualitative evaluation, carried out between 05/28/2021 and 06/21/2021. Scientific articles were searched, from 2019 to 2020, in SciVerse Scopus, Web of Science, PubMed and SCIELO databases. As a result, it was possible to observe that the most commonly used drugs for prophylaxis, and therapeutic of thrombotic events, in patients with COVID-19 were low molecular weight heparin, unfractionated heparin, fondaparinux, oral anticoagulants, antiplatelet agents, argatroban, aspirin, rosuvastatin, vitamin K antagonists, alteplase and other unspecified oral anticoagulants, used in monotherapy or associated. The proposed therapeutic schemes are a variation of the dosage of the drugs used. The use of therapeutic dose (tAC) and prophylactic dose (pAC); tAC, pAC and intermediate dose (iAC); pAC and subtherapeutic dose (subtAC); pAC, subtAC, therapeutic dose of antiplatelet (tAP) and prophylactic dose of antiplatelet (pAP) were found. The drugs used, with the exception of aspirin, showed some type of beneficial response in the recovery of the patient with COVID-19. The best treatment used was therapeutic dosing with enoxaparin, argatroban, fondaparinux and oral anticoagulants. According to the articles evaluated in this review, promising results of the use of antithrombotic agents in C0VID-19 are observed, but more studies are needed. DOI:https://doi.org/10.56238/innovhealthknow-018